IP Case Law Development (Journal of Intellectual Property Rights (JIPR), 2024)
The Supreme Court of India (the Supreme Court) not only declares law while answering the question(s) before it but also declares, and makes and unmakes law. The question(s) of law or fact, or mixed question of law and fact, answered by the Supreme Court becomes binding by virtue of Article 141 of the Constitution of India. By answering such questions, the Court also irons out the creases of law by interpreting-constructing the statutory texts. This article covers the reportable intellectual property (IP) decisions of the Supreme Court delivered in the year 2023. The reportable decisions of the Supreme Court have been taken from Judgement Information System (JUDIS) and Supreme Court Cases.